2020
DOI: 10.1038/s41598-020-62017-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Infrared Irradiation-Assisted Nanosecond-Pulsed Tumor Ablation

Abstract: nanosecond pulsed electric fields (nspef) have the potential to treat a variety of cancer types including melanoma, pancreatic and lung squamous cancers. Recent studies show that nsPEF-based cancer therapy may be improved further with the assistance of moderate heating of the target. A feedbacklooped heating system, utilizing a 980-nm fiber optic laser, was integrated into nsPEF electrodes for tumor ablation. The laser beam profile was determined to be Gaussian using a knife-edge technique. Thermal properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When the application of moderate heating and electric field is combined, these effects are more pronounced and delivery is more efficient. Moderate heating is also advantageous in the context of irreversible elec troporation, where the applied heat sensitizes cancer cells to the applied electric field, thus making a more effective treatment [48,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…When the application of moderate heating and electric field is combined, these effects are more pronounced and delivery is more efficient. Moderate heating is also advantageous in the context of irreversible elec troporation, where the applied heat sensitizes cancer cells to the applied electric field, thus making a more effective treatment [48,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Thermal properties of biological targets are evaluated according to the treatment area, penetration depth, and heat distribution due to laser irradiation with nsPEF. The system provides a detailed thermal analysis of pig skin with infrared laser irradiation and is validated in a tumor-bearing mouse model [137].…”
Section: Thermal Therapymentioning
confidence: 99%
“…Instead, it induces apoptosis of tumour cells and inhibits tumour angiogenesis. As of today, nsPEF has been widely used to treat a great number of cancers, including malignant melanoma (Chen et al, 2010;Rossi et al, 2019;Zhang et al, 2019), skin basal cell carcinoma (Yang et al, 2011), lung squamous cell cancer (Hornef et al, 2020), as well as skin squamous cell carcinoma (Yin et al, 2012). Previous studies have reported the treatment of HCC with nsPEF in animal models since nsPEF does not cause direct Joel heating but induces complete cancer cell death (Yin et al, 2014;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%